Silicon / graphite composite material, preparation method thereof and lithium ion battery containing silicon / graphite composite material
By using silicon/graphite composite materials in lithium-ion batteries and combining low-temperature coating, the problems of poor volume expansion and cycle stability of silicon-based negative electrode materials are solved, and the high energy density and rate performance are improved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411520988.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing silicon-based negative electrode materials are difficult to meet the needs of high energy density and high-speed current charging due to poor volume expansion and cycle stability in lithium-ion batteries. The commonly used silicon-carbon composite materials are secondary growth of silicon crystals at high temperatures. This leads to poor circulation stability.
Using silicon/graphite composite materials, by mixing graphite and silicon materials, and covering the surface with carbon layers, controlling the content and particle size of graphite and silicon, and using low-temperature coating method to prevent the secondary growth of silicon crystals and improve cycle stability sex.
It effectively improves the energy density and rate performance of silicon-based negative electrode materials, reduces the volume expansion of silicon materials, enhances the circulation performance, and simplifies operations through low-temperature processes, reduces costs, and is suitable for industrial mass production.
Smart Images

Figure CN119230794A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a silicon / graphite composite material, a preparation method thereof and a lithium ion battery comprising the same. Background Art
[0002] Graphite has become the most commonly used commercial negative electrode material for lithium-ion batteries due to its low cost, high chemical stability and good processing performance. However, with the development of electric vehicles and energy storage, the theoretical capacity of existing graphite materials has reached its limit and the small theoretical interlayer spacing of graphite cannot meet the needs of high energy density and high-rate current charging. The large rate causes surface lithium deposition and destruction of graphite structure, resulting in a decrease in battery capacity and cycle performance. Silicon materials are expected to become one of the negative electrode materials for high-energy lithium-ion batteries that can replace graphite due to their extremely high theoretical specific capacity (4200mAh / g) and abundant resources. However, silicon materials undergo huge volume changes during the process of lithium insertion / extraction, which will lead to the pulverization and shedding of active materials, and then cause a sharp decrease in the capacity of silicon-based negative electrode batteries.
[0003] The commonly used simple optimization scheme is to combine silicon material with a certain proportion of graphite material to obtain silicon@graphite composite negative electrode material. Unfortunately, although the energy density of this material is greatly improved, the problem of battery performance attenuation caused by the poor conductivity of silicon material and huge volume expansion is still severe. CN116314719A discloses a silicon-carbon composite negative electrode material, its preparation method and application, and lithium-ion battery. The silicon-carbon composite negative electrode material is a powder, including graphite, nano-silicon coated with an amorphous carbon layer formed by phenolic resin-derived carbon, and an amorphous carbon matrix, wherein the nano-silicon is fused and embedded in the graphite surface and the lamella, and the graphite is distributed in the amorphous carbon matrix. The prepared silicon-carbon composite negative electrode material has a relatively high first coulomb efficiency and long cycle stability, and exhibits better electrochemical comprehensive performance under the optimized raw material ratio conditions. However, the high temperature (800-1000°C) of the carbon coating pyrolysis process inevitably leads to secondary growth of silicon crystals, which in turn leads to a large volume expansion of the silicon material in the composite material and poor cycle stability.
[0004] Therefore, how to provide a silicon-based composite material in which silicon material and graphite material are evenly mixed and dispersed, have good contact, and can solve the problems of high expansion, poor cyclic stability and low compaction density of silicon material has become a problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a silicon / graphite composite material, a preparation method thereof and a lithium ion battery comprising the same.
[0006] In a first aspect, the present invention provides a silicon / graphite composite material, the silicon / graphite composite material comprising a mixed material and a carbon coating layer coated on the surface of the mixed material;
[0007] The mixed material includes graphite material and silicon material;
[0008] In terms of mass percentage, in the mixed material, the content of the graphite material is 80-95wt%, and the content of the silicon material is 5-20wt%;
[0009] The thickness of the carbon coating layer is 50-300 nm;
[0010] The D50 particle size of the graphite material is 2-10 μm;
[0011] The D50 particle size of the silicon material is 0.5-3 μm;
[0012] The D50 particle size of the silicon / graphite composite material is 12-30 μm.
[0013] In some embodiments of the present invention, the D50 particle size of the graphite material is 4-8 μm.
[0014] In some embodiments of the present invention, the D50 particle size of the silicon material is 1-3 μm.
[0015] In some embodiments of the present invention, the graphite material includes artificial graphite and / or natural graphite.
[0016] In some embodiments of the present invention, the artificial graphite includes but is not limited to one or more of artificial graphite sheets, artificial graphite balls or artificial graphite blocks.
[0017] In some embodiments of the present invention, the natural graphite includes but is not limited to natural flake graphite and / or natural graphite blocks.
[0018] In some embodiments of the present invention, the silicon material includes but is not limited to one or more of silicon element, silicon-oxygen material, pre-lithium silicon-oxygen material, pre-magnesium silicon-oxygen material or silicon-carbon material.
[0019] In some embodiments of the present invention, the preparation method of the silicon-carbon material includes but is not limited to a ball milling method or a CVD vapor deposition method.
[0020] Among them, CVD vapor deposition method includes:
[0021] S1: crushing porous carbon;
[0022] S2: heating the crushed porous carbon in a protective atmosphere, then introducing a silicon source gas to deposit silicon, controlling the temperature to be 600-800° C., to obtain a first precursor;
[0023] S3: placing the first precursor in a carbon source gas for pyrolysis at a pyrolysis temperature of 600-800° C. to obtain a silicon-carbon material.
[0024] The choice of silicon source gas is not particularly limited. For example, it may be one or more of monosilane, disilane, dichlorosilane or trichlorosilane.
[0025] The choice of carbon source gas is not particularly limited, and illustratively, it may be one or more of methane, acetylene, ethylene or propylene.
[0026] In some embodiments of the present invention, the thickness of the carbon coating layer is 150-250 nm.
[0027] In some embodiments of the present invention, in the Raman spectrum of the carbon coating layer, 0.4≤ID / IG≤0.7, preferably 0.45≤ID / IG≤0.65.
[0028] In a second aspect, the present invention provides a method for preparing the silicon / graphite composite material as described in the first aspect, the preparation method comprising the following steps:
[0029] (1) performing a first mixing of a graphite material and a silicon material to obtain a mixed dry material;
[0030] (2) performing a second mixing of the mixed dry material obtained in step (1) and a coating agent, and then granulating and coating the mixed dry material to obtain a silicon / graphite composite material precursor;
[0031] (3) carbonizing the silicon / graphite composite material precursor obtained in step (2) to obtain a silicon / graphite composite material;
[0032] The temperature of the carbonization treatment is 300-500°C.
[0033] In some embodiments of the present invention, the time of the first mixing in step (1) is 20-60 min, preferably 30-40 min.
[0034] In some embodiments of the present invention, the time of the second mixing in step (2) is 10-60 min, preferably 20-40 min.
[0035] In some embodiments of the present invention, the coating agent in step (2) includes but is not limited to coal tar and / or petroleum tar.
[0036] In some embodiments of the present invention, the equipment used for the granulation coating in step (2) includes but is not limited to any one of a rotary barrel carbon coating equipment, a fluidized bed spraying carbon coating equipment, a spray dryer or a particle granulator.
[0037] In some embodiments of the present invention, the temperature of the carbonization treatment in step (3) is 400-500°C.
[0038] In some embodiments of the present invention, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, preferably 5-8°C / min.
[0039] In some embodiments of the present invention, the holding time of the carbonization treatment in step (3) is 100-200 minutes.
[0040] In some embodiments of the present invention, the carbonization treatment in step (3) is performed under a protective atmosphere.
[0041] In a third aspect, the present invention provides a negative electrode plate for a lithium-ion battery, comprising the silicon / graphite composite material as described in the first aspect, or the silicon / graphite composite material prepared by the preparation method as described in the second aspect.
[0042] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet of a lithium ion battery as described in the third aspect, comprising:
[0043] (1) mixing a negative electrode active material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry;
[0044] The negative electrode active material includes the silicon / graphite composite material and a graphite material;
[0045] (2) The negative electrode slurry obtained in step (1) is coated on the front and back surfaces of the negative electrode current collector to form a coating layer, which is then dried, rolled and cut in sequence to obtain a negative electrode sheet for a lithium-ion battery.
[0046] In some embodiments of the present invention, step (1) specifically comprises: first mixing the silicon / graphite composite material and a portion of the conductive agent to obtain a premixed dry material;
[0047] performing a second mixing of the binder and a portion of the solvent to obtain a binder solution;
[0048] The premixed dry material, the remaining conductive agent, part of the binder solution and the remaining solvent are mixed for the third time to obtain a first mixed solution; the first mixed solution and the remaining binder solution are mixed for the fourth time to obtain a negative electrode slurry.
[0049] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotube or graphene.
[0050] In some embodiments of the present invention, the binder includes but is not limited to carboxymethyl cellulose (CMC) and / or polyacrylic acid (PAA).
[0051] In some embodiments of the present invention, the solvent comprises water.
[0052] In some embodiments of the present invention, in the negative electrode slurry, the mass proportion of the negative electrode active material is 90-96wt%, the mass proportion of the conductive agent is 1.5-5wt%, and the mass proportion of the binder is 2-5wt%; the solid content of the negative electrode slurry is 40-50%.
[0053] In some embodiments of the present invention, the negative electrode current collector includes but is not limited to copper foil or graphene paper.
[0054] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery negative electrode sheet as described in the third aspect.
[0055] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:
[0056] (1) The present invention mixes graphite material and silicon material and coats them with a carbon layer. By further selecting appropriate content and particle size of graphite material, content and particle size of silicon material and particle size of the obtained silicon / graphite composite material, the gram capacity of silicon-based negative electrode material is effectively improved, while the volume expansion of silicon material is reduced, thereby enhancing the rate performance and cycle performance of the composite material.
[0057] (2) The present invention prepares the silicon / graphite composite material by a low-temperature coating method, which effectively inhibits the secondary growth of silicon crystals in the silicon material and improves the cycle stability of the battery cell. The process operation is simple and the cost is low, which is conducive to industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 A schematic structural diagram of the silicon / graphite composite material provided for a specific embodiment of the present invention.
[0059] Among them, 1-graphite material; 2-silicon material; 3-carbon coating layer. DETAILED DESCRIPTION
[0060] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0061] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0063] In a first aspect, the present invention provides a silicon / graphite composite material, the silicon / graphite composite material comprising a mixed material and a carbon coating layer coated on the surface of the mixed material;
[0064] The mixed material includes graphite material and silicon material;
[0065] In terms of mass percentage, in the mixed material, the content of the graphite material is 80-95wt%, and the content of the silicon material is 5-20wt%;
[0066] Among them, the content of graphite material can be selected as 80wt%, 90wt%, 92wt% or 95wt% etc.; the content of silicon material can be selected as 5wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt% etc., but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0067] The thickness of the carbon coating layer is 50-300 nm;
[0068] The thickness of the carbon coating layer may be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm or 300 nm, but is not limited to the listed values, and other values not listed within the range are also applicable;
[0069] The D50 particle size of the graphite material is 2-10 μm;
[0070] The D50 particle size of the silicon material is 0.5-3 μm;
[0071] The D50 particle size of the silicon / graphite composite material is 12-30 μm;
[0072] Among them, the D50 particle size of the graphite material can be 2μm, 4μm, 6μm, 8μm or 10μm, etc.; the D50 particle size of the silicon material can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm or 3μm, etc.; the D50 particle size of the silicon / graphite composite material can be 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm or 30μm, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0073] In the prior art, graphite particles (primary particles) are compacted well but have poor rate performance. The present invention reduces the particle size of graphite materials and uses amorphous carbon as a bonding material to prepare graphite secondary particles, thereby increasing the anisotropy of graphite materials, lithium ion diffusion pathways and rate performance of the materials. At the same time, by adding a proper amount of silicon material, the volume expansion is controlled to avoid reducing the cycle performance and rate performance of the material. On the other hand, a proper amount of silicon material increases the gram capacity of the composite material, effectively improving the energy density of the battery, which is conducive to promoting the development of silicon-based negative electrode batteries.
[0074] In addition, the excellent comprehensive performance of silicon / graphite composite materials is not limited to the control of the particle size of graphite materials, but also requires the appropriate particle size of silicon materials. If the particle size of graphite materials and silicon materials is small, the specific surface area and active sites of the resulting composite materials will increase, which will lead to the occurrence of side reactions and the increase of irreversible lithium, reduce the first effect, and the side reactions will intensify at high temperatures, resulting in deterioration of high-temperature cycle performance. If the particle size of graphite materials and silicon materials is large, the particle size of the resulting composite material is too large, which will increase the ion transmission path and reduce the porosity, which is not conducive to the infiltration of electrolytes and ion diffusion, thereby reducing the fast charging performance of the battery.
[0075] In some embodiments of the present invention, the D50 particle size of the graphite material is 4-8 μm, such as 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0076] And / or, the D50 particle size of the silicon material is 1-3 μm, such as 1 μm, 2 μm or 3 μm, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0077] In some embodiments of the present invention, the graphite material includes but is not limited to artificial graphite and / or natural graphite.
[0078] In some embodiments of the present invention, the artificial graphite includes but is not limited to one or more of artificial graphite sheets, artificial graphite balls or artificial graphite blocks.
[0079] In some embodiments of the present invention, the natural graphite includes but is not limited to natural flake graphite and / or natural graphite blocks.
[0080] In some embodiments of the present invention, the silicon material includes but is not limited to one or more of silicon element, silicon oxide material, pre-lithium silicon oxide material, pre-magnesium silicon oxide material or silicon carbon material, such as a combination of silicon element and silicon oxide material, a combination of silicon oxide material and silicon carbon material, etc.
[0081] In some embodiments of the present invention, the preparation method of the silicon-carbon material includes but is not limited to a ball milling method or a CVD vapor deposition method.
[0082] Among them, CVD vapor deposition method includes:
[0083] S1: crushing porous carbon;
[0084] S2: heating the crushed porous carbon in a protective atmosphere, then introducing a silicon source gas to deposit silicon, controlling the temperature to be 600-800° C., to obtain a first precursor;
[0085] S3: placing the first precursor in a carbon source gas for pyrolysis at a pyrolysis temperature of 600-800° C. to obtain a silicon-carbon material.
[0086] The temperature of step S2 may be 600° C., 650° C., 700° C., 750° C. or 800° C., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0087] The pyrolysis temperature of step S3 may be 600°C, 650°C, 700°C, 750°C or 800°C, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0088] The choice of silicon source gas is not particularly limited. For example, it can be one or more of monosilane, disilane, dichlorosilane or trichlorosilane, such as a combination of monosilane and disilane, a combination of dichlorosilane and trichlorosilane, etc.
[0089] The choice of carbon source gas is not particularly limited. For example, it can be one or more of methane, acetylene, ethylene or propylene, such as a combination of methane and acetylene, a combination of ethylene and propylene, and the like.
[0090] In some embodiments of the present invention, the thickness of the carbon coating layer is 150-250 nm, such as 150 nm, 200 nm or 250 nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0091] Reasonable carbon coating thickness can alleviate the problems caused by volume expansion and help improve the rate performance and stability of composite materials.
[0092] In some embodiments of the present invention, in the Raman spectrum of the carbon coating layer, 0.4≤ID / IG≤0.7, for example 0.4, 0.5, 0.6, 0.7 or 0.8, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 0.45≤ID / IG≤0.65.
[0093] ID / IG represents the degree of defects in carbon materials. The ID / IG of graphite materials is generally between 0.1 and 0.3. The low-temperature carbon coating is amorphous carbon, and due to the low formation temperature, it has more defects and active sites, which are conducive to the adsorption of lithium ions and are beneficial to fast charging performance. However, too many defects and active sites will cause the irreversible lithium in the first cycle to increase and the first efficiency to decrease. Therefore, ensuring a reasonable ID / IG range for the carbon coating will help improve the fast charging performance and first efficiency of the battery.
[0094] In a second aspect, the present invention provides a method for preparing the silicon / graphite composite material as described in the first aspect, the preparation method comprising the following steps:
[0095] (1) performing a first mixing of a graphite material and a silicon material to obtain a mixed dry material;
[0096] (2) performing a second mixing of the mixed dry material obtained in step (1) and a coating agent, and then granulating and coating the mixed dry material to obtain a silicon / graphite composite material precursor;
[0097] (3) carbonizing the silicon / graphite composite material precursor obtained in step (2) to obtain a silicon / graphite composite material;
[0098] The temperature of the carbonization treatment is 300-500°C. The temperature of the carbonization treatment can be 300°C, 350°C, 400°C, 450°C or 500°C, but is not limited to the listed values. Other values not listed in this range are also applicable.
[0099] The present invention prepares the silicon / graphite composite material by a low-temperature coating method, which effectively inhibits the secondary growth of silicon crystals in the silicon material and improves the cycle stability of the battery core. The process operation is simple and the cost is low, which is conducive to industrial mass production.
[0100] In some embodiments of the present invention, the time of the first mixing in step (1) is 20-60 min, for example, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 30-40 min.
[0101] In some embodiments of the present invention, the time of the second mixing in step (2) is 10-60 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 20-40 min.
[0102] In some embodiments of the present invention, the coating agent in step (2) includes coal tar and / or petroleum tar.
[0103] In some embodiments of the present invention, the equipment used for the granulation coating in step (2) includes but is not limited to any one of a rotary barrel carbon coating equipment, a fluidized bed spraying carbon coating equipment, a spray dryer or a particle granulator.
[0104] In some embodiments of the present invention, the temperature of the carbonization treatment in step (3) is 400-500°C, such as 400°C, 450°C or 500°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0105] In some embodiments of the present invention, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 5-8°C / min.
[0106] In some embodiments of the present invention, the holding time of the carbonization treatment in step (3) is 100-200 min, for example, 100 min, 120 min, 140 min, 160 min, 180 min or 200 min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0107] In some embodiments of the present invention, the carbonization treatment in step (3) is performed under a protective atmosphere.
[0108] In some embodiments of the present invention, the protective atmosphere includes any one of an argon atmosphere, a helium atmosphere or a neon atmosphere.
[0109] In a third aspect, the present invention provides a negative electrode plate for a lithium-ion battery, comprising the silicon / graphite composite material as described in the first aspect, or the silicon / graphite composite material prepared by the preparation method as described in the second aspect.
[0110] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet of a lithium ion battery as described in the third aspect, comprising:
[0111] (1) mixing a negative electrode active material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry;
[0112] The negative electrode active material includes the silicon / graphite composite material and a graphite material;
[0113] (2) The negative electrode slurry obtained in step (1) is coated on the front and back surfaces of the negative electrode current collector to form a coating layer, which is then dried, rolled and cut in sequence to obtain a negative electrode sheet for a lithium-ion battery.
[0114] In some embodiments of the present invention, step (1) specifically comprises: first mixing the silicon / graphite composite material and a portion of the conductive agent to obtain a premixed dry material;
[0115] performing a second mixing of the binder and a portion of the solvent to obtain a binder solution;
[0116] The premixed dry material, the remaining conductive agent, part of the binder solution and the remaining solvent are mixed for the third time to obtain a first mixed solution; the first mixed solution and the remaining binder solution are mixed for the fourth time to obtain a negative electrode slurry.
[0117] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotube or graphene.
[0118] In some embodiments of the present invention, the binder includes but is not limited to carboxymethyl cellulose (CMC) and / or polyacrylic acid (PAA).
[0119] In some embodiments of the present invention, the solvent comprises water.
[0120] In some embodiments of the present invention, in the negative electrode slurry, the mass proportion of the negative electrode active material is 90-96wt%, for example, 90wt%, 92wt%, 94wt% or 96wt%, etc.; the mass proportion of the conductive agent is 1.5-5wt%, for example, 1.5wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc.; the mass proportion of the binder is 2-5wt%, for example, 2wt%, 3wt%, 4wt% or 5wt%, etc.; the solid content of the negative electrode slurry is 40-50%, for example, 40%, 42%, 44%, 46%, 48% or 50%, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0121] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery negative electrode sheet as described in the third aspect.
[0122] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its applications. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0123] If no specific techniques or conditions are specified in the examples, the conventional techniques or conditions in the art, or the techniques or conditions described in the literature, or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0124] The embodiment of the present invention provides a silicon / graphite composite material and a preparation method thereof. The structural schematic diagram of the silicon / graphite composite material is as shown in Figure 1 As shown. The silicon / graphite composite material comprises a mixed material; the mixed material comprises a graphite material 1 and a silicon material 2;
[0125] The silicon / graphite composite material further comprises a carbon coating layer 3 coated on the surface of the mixed material;
[0126] In terms of mass percentage, in the mixed material, the content of the graphite material 1 is denoted as α1, satisfying 80≤α1≤95wt%, and the content of the silicon material 2 is denoted as α2, satisfying 5≤α2≤20wt%;
[0127] The thickness of the carbon coating layer 3 is denoted as d, which satisfies 50≤d≤300nm;
[0128] The D50 particle size of the graphite material 1 is denoted as D1, satisfying 2≤D1≤10 μm;
[0129] The D50 particle size of the silicon material 2 is denoted as D2, satisfying 0.5≤D2≤3μm;
[0130] The D50 particle size of the silicon / graphite composite material is recorded as D3, and satisfies 12≤D3≤30 μm.
[0131] The graphite material 1 includes artificial graphite and / or natural graphite.
[0132] The silicon material 2 includes one or more of silicon element, silicon-oxygen material, pre-lithium silicon-oxygen material, pre-magnesium silicon-oxygen material or silicon-carbon material.
[0133] In the Raman spectrum of the carbon coating layer 3, 0.4≤ID / IG≤0.7.
[0134] Wherein, the median particle size of each material in the present invention is the volume median particle size. The volume median particle size D50 is obtained using a laser diffraction particle size analyzer (MS2000). The determination method includes: dispersing the sample particles in a liquid medium at a concentration of 200-300 mg / L, and allowing a monochromatic light beam to pass therethrough. After the light is scattered by the particles, it is distributed at different angles, and the regular multi-element detector receives the values of the relevant scattering diagram at many angles, and records these values for analysis. Then, the Rayleigh scattering formula is used to calculate the scattering values, and the ratio of the particle volume of each particle size level to the total volume is obtained, thereby obtaining the volume distribution of the particle size.
[0135] The preparation method comprises the following steps:
[0136] (1) performing a first mixing of graphite material 1 and silicon material 2 for a mixing time of 20-60 min to obtain a mixed dry material;
[0137] (2) performing a second mixing of the mixed dry material obtained in step (1) and the coating agent for a mixing time of 10-60 min, and then granulating and coating to obtain a silicon / graphite composite material precursor;
[0138] (3) Under a protective atmosphere, the silicon / graphite composite material precursor obtained in step (2) is carbonized at 300-500° C., the heating rate is controlled to be 2-10° C. / min, and the holding time is 100-200 min to obtain a silicon / graphite composite material.
[0139] Examples 1-12 and Comparative Examples 1-8 provide a silicon / graphite composite material and a preparation method thereof, respectively. The silicon / graphite composite material refers to the silicon / graphite composite material in the specific implementation manner, and the condition parameters of the obtained silicon / graphite composite material are shown in Table 1. The preparation method refers to the preparation method in the specific implementation manner, and the specific condition parameters are shown in Table 2.
[0140] The graphite materials used in Examples 1-12 and Comparative Examples 1-8 are the same commercial artificial block graphite, and graphite materials with different particle sizes are obtained by screening with a classifier.
[0141] The silicon material used in Examples 1-12 and Comparative Examples 1-8 is a silicon-carbon material, and the preparation method thereof includes:
[0142] S1: crushing the biomass porous carbon;
[0143] S2: The crushed biomass porous carbon is heated in a protective atmosphere, and then silicon source gas (monosilane) is introduced to perform silicon deposition, and the temperature is controlled at 700° C. to obtain a first precursor;
[0144] S3: placing the first precursor in a carbon source gas (methane) for pyrolysis at a pyrolysis temperature of 700° C. to obtain a silicon-carbon material having a silicon content of 45 wt % and a carbon content of 55 wt %.
[0145] Silicon-carbon materials of different particle sizes are obtained through a classifier.
[0146] Table 1 Parameters of silicon / graphite composite materials
[0147]
[0148]
[0149] Table 2 Preparation method parameters
[0150]
[0151]
[0152] Performance Testing
[0153] Preparation of a lithium-ion battery for testing
[0154] Preparation of negative electrode sheet: 96wt% of the silicon / graphite composite material prepared in the embodiment and the comparative example, 1.5wt% of single-walled carbon nanotubes, 2wt% of polyacrylic acid and 0.5wt% of carboxymethyl cellulose were mixed with water to obtain a negative electrode slurry with a solid content of 45%; the obtained negative electrode slurry was transferred to a coating machine, coated on the upper and lower surfaces of the copper foil, and then dried, compacted and cut in sequence to obtain a negative electrode sheet; wherein the thickness of the negative electrode active layer on each side was 45μm, and the surface density was 140mg / 10cm 2 ;
[0155] Preparation of positive electrode sheet: 96wt% positive electrode active material (commercial high nickel ternary, NCM811), 2.5wt% conductive carbon nanotubes, 1.5wt% polyvinylidene fluoride and N-methylpyrrolidone were mixed evenly and filtered with a 200-mesh filter; the obtained positive electrode slurry was transferred to a coating machine, coated on the upper and lower surfaces of aluminum foil, and then dried, compacted and cut in sequence to obtain a positive electrode sheet; wherein the thickness of the positive electrode active layer on each side is 43μm, and the surface density is 290mg / 10cm 2 ;
[0156] Diaphragm: Polypropylene film is used as the diaphragm with a thickness of 14 μm;
[0157] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (EDC) were mixed in a volume ratio of 1:1:1, and then 1 mol / L LiPF6 was added and mixed evenly to prepare an electrolyte;
[0158] The positive electrode sheet to be assembled, the separator, and the negative electrode sheet to be assembled are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a bare battery cell; the bare battery cell is placed in a battery casing, and after drying, an electrolyte is injected, and vacuum packaging, standing, forming and shaping processes are sequentially performed to obtain a lithium-ion battery.
[0159] It should be noted that the above-mentioned test lithium-ion battery is only an example listed for testing the performance of silicon-carbon materials, and the present invention is not limited to this type of battery, wherein the raw materials (except silicon-carbon materials), proportions, parameters and processes can be replaced with other conventional raw materials, proportions, parameters and processes in the art, thereby forming a battery different from the test lithium-ion battery.
[0160] 1. Dynamic performance (fast charging performance) test
[0161] Lithium deposition test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged and discharged at a rate of 4C, with a charge cut-off voltage of 4.4V and a discharge cut-off voltage of 2.5V. After repeating 10 times, the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. Among them, the area of lithium deposition on the surface of the negative electrode plates is less than 5%, which is considered to be slight lithium deposition; the area of lithium deposition on the surface of the negative electrode plates is 5%-40%, which is considered to be moderate lithium deposition; the area of lithium deposition on the surface of the negative electrode plates is greater than 40%, which is considered to be severe lithium deposition.
[0162] 2. First-effect test
[0163] At 25° C., the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 0.33C and discharged at a rate of 0.33C, with a charge cutoff voltage of 4.4 V and a discharge cutoff voltage of 2.5 V. A full charge and discharge cycle test was performed.
[0164] Wherein, first efficiency % = first discharge capacity / first charge capacity×100%.
[0165] 3. Normal temperature cycle performance test
[0166] At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 1C and discharged at a rate of 1C, with a charging cut-off voltage of 4.4V and a discharging cut-off voltage of 2.5V. Full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0167] 4. High temperature cycle performance test
[0168] At 45°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 1C and discharged at a rate of 1C, with a charging cut-off voltage of 4.4V and a discharging cut-off voltage of 2.5V. Full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0169] 5. Actual energy density test
[0170] At 25°C, the lithium ion batteries prepared in the embodiments and comparative examples were fully charged at a rate of 0.33C and fully discharged at a rate of 0.33C. The charge cut-off voltage was 4.3V, and the discharge cut-off voltage was 2.5V. The actual discharge energy at this time was recorded. At 25°C, the lithium ion batteries were weighed using an electronic balance, and the weighing results were recorded as the weight of the lithium ion batteries. The energy density of the lithium ion battery is the ratio of the actual discharge energy to the weight of the lithium ion battery.
[0171] The results of the above performance tests are shown in Table 3.
[0172] Table 3 Performance test results
[0173]
[0174] It can be seen from the test results in the examples and comparative examples that the lithium-ion battery prepared by using the silicon and graphite composite material of the present invention has excellent energy density, kinetic performance and cycle performance.
[0175] In Comparative Example 1, due to the smaller particle sizes of graphite and silicon materials, the specific surface area and active sites increase, which leads to the occurrence of side reactions and the increase of irreversible lithium, thereby reducing the first efficiency and energy density; and the side reactions intensify at high temperatures, resulting in the deterioration of high-temperature cycle performance.
[0176] In Comparative Example 2, due to the large particle sizes of graphite material and silicon material, the particle size of silicon / graphite composite material (secondary particles) is too large, which leads to an increase in ion transmission path and a decrease in porosity, which is not conducive to the infiltration of electrolyte and ion diffusion. After rate testing, the lithium-ion battery has severe lithium deposition on the interface and the fast charging performance is significantly reduced.
[0177] Comparative Example 3 Due to the excessive content of silicon material, although the silicon / graphite composite material has the highest gram capacity and the lithium-ion battery has the highest energy density, its first efficiency is low, the room temperature and high temperature cycle stability is poor, and the fast charge interface lithium precipitation is serious. The reason is that due to the serious intrinsic problems of silicon materials, huge volume expansion will occur during the cycle, causing the material to break. Therefore, when the content of silicon material in the composite material is too large, its volume expansion cannot be effectively suppressed, which makes the cycle stability worse. And the silicon material has poor rate performance, which leads to serious lithium precipitation in the composite material.
[0178] Comparative Example 4 does not contain silicon material and has the best cycle stability, but the energy density is too small, which is not conducive to practical application.
[0179] In Comparative Example 5, due to the small thickness of the carbon coating layer, the room temperature cycle stability and high temperature cycle stability of the lithium ion battery are poor. This is because the too thin carbon coating layer cannot effectively isolate the direct contact between the electrolyte and the silicon material, nor can it inhibit the expansion of the silicon material, and the side reactions increase significantly, resulting in the deterioration of the cycle stability of the composite material. In addition, due to the lack of amorphous carbon, the rate performance of the composite material is significantly deteriorated.
[0180] In Comparative Example 6, the carbon coating layer is too thick and has many defects and active sites, which leads to an increase in irreversible lithium in the first cycle and an intensification of side reactions during high-temperature cycling, which in turn leads to low first efficiency and poor high-temperature cycling performance.
[0181] The Raman ID / IG of carbon materials represents the degree of defects. The Raman ID / IG of the carbon coating layer of the silicon / graphite composite material in Comparative Example 7 is too small, with fewer active sites and defects, resulting in severe lithium deposition at the fast charging interface of the lithium-ion battery, and the inability to effectively improve the ion diffusion rate of the composite material, resulting in poor fast charging performance.
[0182] The Raman ID / IG of the carbon coating layer of the silicon / graphite composite material in Comparative Example 8 is too large, and there are many active sites and defects, which can effectively improve the ion diffusion rate of the composite material. However, it will lead to an increase in the first irreversible lithium and an increase in the cycle side reactions, thereby reducing the first effect and deteriorating the high temperature performance.
[0183] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0184] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A silicon / graphite composite material, characterized in that: The silicon / graphite composite material comprises a mixed material and a carbon coating layer coated on the surface of the mixed material; The mixed material includes graphite material and silicon material; In terms of mass percentage, in the mixed material, the content of the graphite material is 80-95wt%, and the content of the silicon material is 5-20wt%; The thickness of the carbon coating layer is 50-300 nm; The D50 particle size of the graphite material is 2-10 μm; The D50 particle size of the silicon material is 0.5-3 μm; The D50 particle size of the silicon / graphite composite material is 12-30 μm.
2. The silicon / graphite composite material according to claim 1, characterized in that: The D50 particle size of the graphite material is 4-8 μm; And / or, the D50 particle size of the silicon material is 1-3 μm.
3. The silicon / graphite composite material according to claim 1 or 2, characterized in that: The graphite material includes artificial graphite and / or natural graphite; And / or, the silicon material includes one or more of silicon element, silicon-oxygen material, pre-lithium silicon-oxygen material, pre-magnesium silicon-oxygen material or silicon-carbon material.
4. The silicon / graphite composite material according to any one of claims 1 to 3, characterized in that: The thickness of the carbon coating layer is 150-250nm; And / or, in the Raman spectrum of the carbon coating layer, 0.4≤ID / IG≤0.7, preferably 0.45≤ID / IG≤0.
65.
5. A method for preparing the silicon / graphite composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) performing a first mixing of a graphite material and a silicon material to obtain a mixed dry material; (2) performing a second mixing of the mixed dry material obtained in step (1) and a coating agent, and then granulating and coating the mixed dry material to obtain a silicon / graphite composite material precursor; (3) carbonizing the silicon / graphite composite material precursor obtained in step (2) to obtain a silicon / graphite composite material; The temperature of the carbonization treatment is 300-500°C.
6. The preparation method according to claim 5, characterized in that: The first mixing time in step (1) is 20-60 min, preferably 30-40 min.
7. The preparation method according to claim 5 or 6, characterized in that: Step (2) the second mixing time is 10-60 min, preferably 20-40 min; And / or, the coating agent in step (2) includes coal tar and / or petroleum tar.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The temperature of the carbonization treatment in step (3) is 400-500°C; And / or, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, preferably 5-8°C / min; And / or, the holding time of the carbonization treatment in step (3) is 100-200 min; And / or, the carbonization treatment in step (3) is carried out under a protective atmosphere.
9. A negative electrode plate for a lithium ion battery, characterized in that: The invention comprises the silicon / graphite composite material as described in any one of claims 1 to 4, or the silicon / graphite composite material prepared by the preparation method as described in claims 5 to 8.
10. A lithium ion battery, characterized in that: Comprising the negative electrode plate of a lithium-ion battery as claimed in claim 9.
Citation Information
Patent Citations
Silicon-carbon composite negative electrode material, preparation method and application thereof, and lithium ion battery
CN116314719A
